A stone in the bone - Matthieu Halfon (Wiley, 2021)
Abstract Primary hyperoxaluria (PH) is a group of diseases due to mutations in genes coding for enzymes involved in oxalate metabolism. Three types of PH are identified depending on the gene mutated. Type 1 is the most frequent with 80% of the cases, while PH2 and PH3 are rarer. The severity of renal involvement varies between the three types. Indeed, between 60% and 80% of PH1 but only 20% of PH2 patients will reach end‐stage kidney disease. In PH3 patients, dialysis is uncommon. Because oxalate clearance is impaired in CKD patients, oxalate can precipitate in various organs leading to systemic oxalosis. We report an uncommon presentation of bone oxalosis associated with hypercalcemia in a dialyzed patient. This report emphasizes the difficulties to diagnose primary hyperoxaluria and the challenge of treating dialyzed patients.